Accumulation and inactivation of avian influenza virus by the filter-feeding invertebrate Daphnia magna - Meixell, Brandt W; Borchardt, Mark A; Spencer, Susan K (Applied and environmental microbiology, 2013)
The principal mode of avian influenza A virus (AIV) transmission among wild birds is thought to occur via an indirect fecal-oral route, whereby individuals are exposed to virus from the environment through contact with virus-contaminated water. AIV can remain viable for an extended time in water; however, little is known regarding the influence of the biotic community (i.e., aquatic invertebrates) on virus persistence and infectivity in aquatic environments. We conducted laboratory experiments to investigate the ability of an aquatic filter-feeding invertebrate, Daphnia magna, to accumulate virus from AIV-dosed water under the hypothesis that they represent a potential vector of AIV to waterfowl hosts. We placed live daphnids in test tubes dosed with low-pathogenicity AIV (H3N8 subtype isolated from a wild duck) and sampled Daphnia tissue and the surrounding water using reverse transcription-quantitative PCR (RT-qPCR) at 3- to 120-min intervals for up to 960 min following dosing. Concentrations of viral RNA averaged 3 times higher in Daphnia tissue than the surrounding water shortly after viral exposure, but concentrations decreased exponentially through time for both. Extracts from Daphnia tissue were negative for AIV by cell culture, whereas AIV remained viable in water without Daphnia present. Our results suggest daphnids can accumulate AIV RNA and effectively remove virus particles from water. Although concentrations of viral RNA were consistently higher in Daphnia tissue than the water, additional research is needed on the time scale of AIV inactivation after Daphnia ingestion to fully elucidate Daphnia's role as a potential vector of AIV infection to aquatic birds.